Electrochemical magnetization switching and energy storage in manganese oxide filled carbon nanotubes - Ottmann, Alexander; Thauer, Elisa; Schneider, Philip; Klingeler, Rüdiger (Scientific reports, 2017)
The ferrimagnetic and high-capacity electrode material Mn3O4 is encapsulated inside multi-walled carbon nanotubes (CNT). We show that the rigid hollow cavities of the CNT enforce size-controlled nanoparticles which are electrochemically active inside the CNT. The ferrimagnetic Mn3O4 filling is switched by electrochemical conversion reaction to antiferromagnetic MnO. The conversion reaction is further exploited for electrochemical energy storage. Our studies confirm that the theoretical reversible capacity of the Mn3O4 filling is fully accessible. Upon reversible cycling, the Mn3O4CNT nanocomposite reaches a maximum discharge capacity of 461 mA h g−1 at 100 mA g−1 with a capacity retention of 90% after 50 cycles. We attribute the good cycling stability to the hybrid nature of the nanocomposite: (1) Carbon encasements ensure electrical contact to the active material by forming a stable conductive network which is unaffected by potential cracks of the encapsulate. (2) The CNT shells resist strong volume changes of the encapsulate in response to electrochemical cycling, which in conventional (i.e., non-nanocomposite) Mn3O4 hinders the application in energy storage devices. Our results demonstrate that Mn3O4 nanostructures can be successfully grown inside CNT and the resulting nanocomposite can be reversibly converted and exploited for lithium-ion batteries.
Gesehen am 28.03.2018